THE ROLE OF THE INFECTIOUS FACTOR IN THE FORMATION OF FETAL GROWTH RETARDATION AND GESTATION OUTCOMES - Куклина, Лариса Владимировна; Кравченко, Елена Николаевна; Кривчик, Галина Владимировна (Mother and Baby in Kuzbass, 2020)
Purpose of the study – to study the features of the course of pregnancy and the outcome of childbirth during intrauterine infection (IUI) in newborns with fetal growth retardation (FGR).Materials and methods. A retrospective analysis of the medical documentation of 157 women who gave birth on the basis of the City Clinical Perinatal Center in Omsk was performed. All patients with FGR were divided into 2 groups, depending on the presence of IUI: the main group – 33 women who gave birth to children with an established diagnosis of FGR and IUI, the comparison group – 124 women who gave birth to children with FGR without IUI.Results. In the main group, the most common pathology during pregnancy was acute respiratory viral infections during pregnancy – in 13 (39,4 %) and kidney diseases in 5 (15,1 %), bacterial vaginosis and bacterial vaginitis in 15 (45,4 %), which was significantly more than in the comparison group – in 25 (20,2 %; p = 0,022), in 5 (4,0 %; p = 0,021) and in 24 (19,3 %; p = 0,003) patients respectively. Most often, in both groups, I degree of FGR occurred, but in the comparison group it was significantly more frequent (77,4 %), III degree of FGR was detected only in the main group in 3 (9,1 %) newborns (p < 0,001). In the main group, 4 (12,1 %) cases of early neonatal mortality were recorded (1 – early sepsis of the newborn, 3 – congenital pneumonia), in the comparison group, cases of early neonatal mortality were not recorded.Conclusion. In pregnant women with fetal growth retardation syndrome who gave birth to newborns with intrauterine infection, genital tract infections, acute and exacerbation of chronic infections of extragenital localization were significantly more often detected. The presence of infection was characterized by a high frequency of critical conditions of the fetus, which led to adverse perinatal outcomes.
Keywords: intrauterine infection (IUI); fetal growth retardation; the course of pregnancy; outcomes of childbirth